2022
DOI: 10.3389/froh.2021.801815
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among Periodontitis, Pneumonia and COVID-19

Abstract: Periodontitis is a chronic inflammatory disease of the supporting structures of the teeth that affects approximately half of adults 30 years and older. There is increasing interest in the direct and indirect relationships between periodontitis and systemic diseases, including respiratory diseases. The aim of this study was to assess the evidence on links among periodontitis, pneumonia, and COVID-19. Oral and periodontal bacteria may be linked to respiratory disease directly by aspiration of pathogens into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
0
9
0
3
Order By: Relevance
“…Periodontal disease, a chronic inflammatory disease, is one of the representative oral diseases and is caused by pathogenic microorganisms, genetic factors, and environmental factors. Periodontal disease is also reported to be closely related to various systemic diseases such as pregnancy side effects, cardiovascular disease, respiratory disease, diabetes, and osteoporosis [17][18][19][20]. However, the pathogenic factors acting on the development process have not been clearly identified, and the effects of extra oral physical factors such as nutritional disorders and metabolic disorders on periodontal disease have not been accurately identified [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease, a chronic inflammatory disease, is one of the representative oral diseases and is caused by pathogenic microorganisms, genetic factors, and environmental factors. Periodontal disease is also reported to be closely related to various systemic diseases such as pregnancy side effects, cardiovascular disease, respiratory disease, diabetes, and osteoporosis [17][18][19][20]. However, the pathogenic factors acting on the development process have not been clearly identified, and the effects of extra oral physical factors such as nutritional disorders and metabolic disorders on periodontal disease have not been accurately identified [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Fusion of these pathogenic viruses begins with the activation of their surface proteins, whether they are S proteins (SARS-CoV-2), influenza virus hemagglutinin (AH1N1), or protein receptors of other viruses. Thus, it can be suggested that blocking cysteine cathepsins (B / L) in the respiratory tract may be used for a wider range of therapies than just SARS-CoV-2 [52] , [53] , [54] , [55] .…”
Section: Discussionmentioning
confidence: 99%
“…Слизистая оболочка полости рта высоковосприимчива к инфекции SARS-CoV-2, что обусловлено широким распространением АПФ2 в ротовой полости, главным образом эпителиальных клетках слизистой оболочки полости рта, фибробластах пародонтальной связки и деснах, и соответственно, может рассматриваться в качестве входных ворот для вируса SARS-CoV-2 и его резервуара [4][5][6][7][8][9][10][11][12].…”
Section: Introductionunclassified